Consumer Inattention and Decision Heuristics: The Causal Effects of Energy Label Elements - Mark Andor; Andreas Gerster; Stephan Sommer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Energy labels have been introduced in many countries to make consumers more attentive to energy use in purchase decisions of durables. Despite their wide application, however, little is known about the effects of specific label designs. In this paper, we explore how energy labels can help to address inattention of consumers to energy efficiency. Our analysis is based on a (randomized controlled) discrete choice experiment among about 5,000 households in which we implement treatments that vary the label design. We find that supplementing the label with annual cost information increases attention to operating cost and promotes the choice of durables with higher energy efficiency. Moreover, simplifying the label has similar positive effects, most notably for individuals with low education. Finally, we show that a substantial share of individuals employ decision heuristics, focusing primarily on efficiency classes while neglecting more detailed information on energy consumption.
Keywords: D12; D83; Q48; 330